2017
DOI: 10.1161/strokeaha.117.017985
|View full text |Cite
|
Sign up to set email alerts
|

Island Sign

Abstract: The island sign is a reliable CT imaging marker that independently predicts hematoma expansion and poor outcome in patients with ICH. The noncontrast CT island sign may serve as a potential marker for therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(41 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…The relatively hypodense area has an identifiable border and a difference of at least 28 HU between the two density regions [12,21]. The IS consists of at least 3 scattered small hematomas all separate from the main hematoma or at least 4 small hematomas some or all of which may connect with the main hematoma [14]. The imaging sign HD was defined as any hypodense region strictly encapsulated within the hemorrhage with any shape, size, and density which does not require a density measurement [6,15,22].…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively hypodense area has an identifiable border and a difference of at least 28 HU between the two density regions [12,21]. The IS consists of at least 3 scattered small hematomas all separate from the main hematoma or at least 4 small hematomas some or all of which may connect with the main hematoma [14]. The imaging sign HD was defined as any hypodense region strictly encapsulated within the hemorrhage with any shape, size, and density which does not require a density measurement [6,15,22].…”
Section: Image Analysismentioning
confidence: 99%
“…To this end, several imaging markers on non-contrast computed tomography (NCCT) have been described to be predictive of hematoma expansion and poor functional outcome [6]. These imaging characteristics include the blend sign (BS) [6,11], the black hole sign (BHS) [6,12,13], the island sign (IS) [6,14], and the more general appearance of hypodensities (HD) [6,15]. In addition, a contrast extravasation on computed tomography angiogram (CTA) within an ICH is referred as the established spot sign [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Third, this was a retrospective clinical study and the sample size was relatively small. In addition, the black hole sign [ 40 ] and the island sign [ 41 ], which also indicate active bleeding, were are not studied and further studies are urgently needed to investigate the associations between hyperglycemia and these signs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous randomized controlled trials reported that <25% of patients with ICH underwent CTA during the acute phase ( 5 , 6 ). Other research studies have reported that a number of indicators are associated with HE and poor outcomes in patients with ICH, including non-contrast CT (NCCT) markers, such as computed tomography (CT) hypodensities ( 7 ), the black hole sign ( 8 ), the blend sign ( 9 ), and the island sign ( 10 ). However, there is an urgent need for further research to identify the prognostic value of biomarkers for HE.…”
Section: Introductionmentioning
confidence: 99%